Prinsip Implementasi Manajemen Strategik dalam Perspektif Islam - Rahmatullah, Rahmatullah (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
The focus of this research is to describe the principles of strategic planning and implementation of an Islamic perspective. The research method used was literature review, where researchers reviewed and studied the literature related to the theme of this research. The result of this study showed that there were several principles of strategic planning and implementation of Islamic perspectives, including the importance of the strategy and the goals of the future (vision, mission, goals, and objectives), the organization had to be solid and orderly, the organization was not fragmented, the importance of deliberation in the organization, the importance of internal and external environmental analysis (SWOT) and the importance of making good policy. Keywords : Strategic Management, Islamic perspective.